FINANCIAL MANAGEMENT PERFORMANCE ANALYSIS PRIVATE UNIVERSITIES - Retno Susanty, Theresia Novie; Trisnawati, Rina; Sasongko, Noer (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to evaluate the performance of financial management in private universities, involving analysis of various aspects of financial management including planning, budgeting, control, and financial reporting. The population in this study consists of private universities in Central Java with campus characteristics willing to participate as research subjects. The sample size is 150 respondents who meet the criteria for the study sample. Sampling technique used is purposive sampling method. The research method employed is a questionnaire with respondents meeting specific criteria: minimum one-year work experience, understanding of financial management in universities, and willingness to participate in the study. Data analysis method used is multiple linear regression analysis with SPSS version 25. The results indicate that Human Resources do not affect Financial Management Performance, Facilities and Infrastructure affect Financial Management Performance, Utilization of Information Technology affects Financial Management Performance, Budgeting System does not affect Financial Management Performance, Regulations affect Financial Management Performance, Level of Training affects Financial Management Performance, and Internal Audit affects Financial Management Performance. Keywords: Human Resources, Facilities and Infrastructure, Utilization of Information Technology, Budgeting System, Regulations, Level of Training, Internal Audit, and Financial Management Performance